Chemical Vapor Deposition Mediated Phase Engineering for 2D Transition Metal Dichalcogenides: Strategies and Applications. Issue 1 (19th October 2021) - Hernandez Ruiz, Karla; Wang, Ziqian; Ciprian, Matteo; Zhu, Meifang; Tu, Rong; Zhang, Lianmeng; Luo, Wei; Fan, Yuchi; Jiang, Wan
Abstract : 2D transition metal dichalcogenides (TMDs) are characterized by the presence of multiple crystal structures or phases, even at the ultrathin limit. Controlling phase transformations, namely, phase engineering, of 2D TMDs is crucial for realizing high‐performance 2D devices by combining phases with distinct physical and chemical properties. As a powerful approach for large‐scale production of high‐quality 2D TMDs, chemical vapor deposition (CVD) offers unique advantages in phase engineering due to its highly controllable synthesis processes. Starting with an introduction of the crystal structures and phase transformations of 2D TMDs, this review summarizes the recent developments in CVD‐mediated phase engineering strategies of TMDs, including control of temperature, precursors, catalysis, atmosphere, composition, and strain during the deposition process. Moreover, the representative applications of CVD‐based phase‐engineered TMDs in the field of transistors, photodetectors, photovoltaic cells, and catalysis are overviewed. Finally, the challenges, expectations of CVD‐based phase engineering, and future development of this versatile technique are discussed. Abstract : A detailed review of the recent development in phase engineering of 2D transition metal dichalcogenides (2D TMDs) by chemical vapor deposition (CVD) technique is presented, in which the CVD‐oriented controlling strategies for various 2D TMDs and representative applications of phase‐selective grown materials in high‐performance devices are highlighted.